A PERSPECTIVE ON ANTIINFECTIVE AGENTS INTERACTION IN HUMAN IMMUNODEFICIENCY VIRUS PATIENTS WITH MALARIAL INFECTION - Bhopale, Girish M (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Despite recent research advances in anti-infective agents (achievements), Human immunodeficiency virus (HIV), and malaria infection are currently considered two main global human health problems. Given the considerable geographical overlap between malaria and HIV, a substantial number of co-infection incidences occur in human. The purpose of this review is to summarize the information on the clinical impact of co-infection, therapeutic anti-infective agents’ interaction in human and future research priorities. Keywords: Malaria, Human immunodeficiency virus, Co-infection, Anti-malarial drug and anti-retroviral drug interaction, Public health, Clinical epidemiology, Anti-infective agents.